AUTC Review of Biotechnology 2003. - Gray, Peter; Barnard, Ross; Franco, Chris; Rifkin, Will; Hine, Damian; Young, Fiona (Australian Universities Teaching Committee, 2003)
This 2003 report is a review of Biotechnology programs on offer in Australian universities commissioned by the Australian Universities Teaching Committee. The report presents a detailed study of programs and makes recommendations for future development.